Anti-inflammatory effects of two lupane-type triterpenes from leaves of Acanthopanax gracilistylus on LPS-induced RAW264.7 macrophages - LUO,Jiao (2022)
Abstract Acanthopanax gracilistylus W.W.Smith (AGS) is an traditional Chinese medicine and its leaves that have rich biological activities has been long used as a fresh vegetable in Chinese folk. There are two lupane-type triterpenoids, 3α,11α-dihydroxy-23-oxo-lup-20(29)-en-28-oic acid (1) and 3α,11α,23-trihydroxy-lup-20(29)-en-28-oic acid (2), were isolated as the active constituents from leaves of AGS. However, the anti-inflammatory effects and potential mechanisms of 1 and 2 on LPS-induced RAW264.7 Macrophages have not been evaluated. In this study, the results shown that compounds 1 and 2 reduced the levels of early pro-inflammatory cytokines TNF-α, IL-1β, the secretion of late pro-inflammatory cytokine HMGB1, as well as the activation of transcription factor NF-κB in RAW 264.7 macrophages induced by LPS. In conclusion, two lupane-type triterpenes (1 and 2) have anti-inflammatory activities in LPS-induced RAW264.7 cells through inhibiting expression of proinflammatory cytokines and NF‐κB activation and could be potentially used in treatment of inflammatory-related diseases in the future.